Struktur Komunitas Makrozoobentos Pada Sedimen Permukaan Pantai Sampur, Kabupaten Bangka Tengah - Kasi Sastra; Mohammad Agung Nugraha; Aditya Pamungkas (Journal of Tropical Marine Science, 2022)
Sampur Beach is one of the beaches in Central Bangka Regency with a tin mining area and capture fisheries. Macrozoobenthos is a relatively large basic object, which is more than 1 mm. This study aims to determine the structure of the macrozoobenthos community (indices of diversity, uniformity, and dominance) on the surface sediments of Sampur Beach, Central Bangka Regency. This research was conducted in February 2021 at Sampur Beach, using a purposive sampling method of 5 stations (3 times in a row). Sampling was carried out using an Ekman grab. The results showed that on the surface sediments of Sampur Beach there were 163 individuals of 12 species from the class Bivalvia and Gastropods spread over 5 observations. The density of macrozoobenthos ranged from 375 - 1525 individuals/m2 and the species composition ranged from 2 - 88%. At the study site, the diversity index (H) values ranged from 0.503 to 1.382, the uniformity index (E) ranged from 0.312 to 0.713, and the dominance index ranged from 0.355 to 0.788. This study shows that the level of macrozoobenthos diversity in the surface sediments of Sampur Beach is low to moderate, the level of uniformity is low to high, and there is no dominant species.